Assessment of financial sustainability of the local budgets: case of Ukraine - Lysiak, Liubov; Лисяк, Любов Валентинівна; Kachula, Svitlana; Качула, Світлана Валентинівна; Hrabchuk, Oksana; Грабчук, Оксана Миколаївна; Filipova, Milena; Філіпова, Мілєна; Kushnir, Anna; Кушнір, Анна Ігорівна (LLC “Consulting Publishing Company “Business Perspectives”, 2020)
With the deepening of global financial and economic instability, the search for ways to increase fiscal sustainability becomes relevant in the crisis regulation system. This problem is compounded by the emergence of new global challenges, including the COVID pandemic. Timely and complex analysis of the local budget financial sustain-ability allows one to comprehensively assess financial and economic risks, identify social and other problems, consider planning deficiencies and, on this basis, form a sound and effective regional budget policy. The purpose of the study is to summarize theoretical and practical principles of assessing the financial sustainability of local budgets and to outline the directions for its improvement in Ukraine considering international practices. The study revealed the lack of a unified system for assessing the financial sustainability of local budgets in Ukraine. On the basis of generalization of theoretical and methodological approaches, a system of indicators for estimating the financial sustainability of local budgets has been identified. The indicators were grouped and calculated. Based on the study of practical experience, measures have been specified that would contribute to a systematic approach to assessing the financial sustainability of local budgets in Ukraine. It was concluded that a systematic assessment of the financial sustainability of local budgets is a prerequisite for making informed management decisions about necessary adjustments to the budget, improving the quality of budget planning and the effectiveness of budget policy. З поглибленням світової фінансово-економічної нестабільності пошук шляхів підвищення фіскальної стійкості стає актуальним у системі врегулювання криз. Ця проблема ускладнюється появою нових глобальних викликів, включаючи пандемію COVID. Своєчасний та складний аналіз фінансової стійкості місцевого бюджету дозволяє всебічно оцінити фінансові та економічні ризики, виявити соціальні та інші проблеми, розглянути недоліки планування та на цій основі сформувати обґрунтовану та ефективну регіональну бюджетну політику. Метою дослідження є узагальнення теоретичних та практичних принципів оцінки фінансової стійкості місцевих бюджетів та окреслення напрямів його вдосконалення в Україні з урахуванням міжнародної практики. Дослідження виявило відсутність єдиної системи оцінки фінансової стійкості місцевих бюджетів в Україні. На основі узагальнення теоретичного та методологічного підходів визначена система показників для оцінки фінансової стійкості місцевих бюджетів. Показники були згруповані та розраховані. На основі вивчення практичного досвіду було визначено заходи, які могли б сприяти системному підходу до оцінки фінансової стійкості місцевих бюджетів в Україні. Було зроблено висновок, що систематична оцінка фінансової стійкості місцевих бюджетів є необхідною умовою прийняття обґрунтованих управлінських рішень про необхідні коригування бюджету, підвищення якості бюджетного планування та ефективності бюджетної політики.
Оцінка фінансової стійкості місцевих бюджетів: приклад України
Keywords: local budget; місцевий бюджет; sustainability; стійкість; assessment; оцінка; borrowing; запозичення; decentralization; децентралізація; fiscal policy; фіскальна політика; planning; планування